OPTIMASI WAKTU DAN BIAYA PROYEK REVITALISASI PASAR KRATON KOTA TEGAL (Magister Teknik Sipil, Fakultas Teknik, Universitas 17 Agustus 1945 Surabaya, 2022)
The Kraton Market Revitalization Project on Jalan Cinde, Kraton Village, Tegal Barat District, Tegal City started on July 28, 2019 and is targeted to be completed on December 28, 2019. However, there has been a delay in the 11th week of 6.9%, so this project has the potential to experience problems. overall delay in completion. To anticipate these delays, efforts are needed to accelerate project completion by analyzing the acceleration of time against costs (Time Cost Trade Off). The consequence of accelerating the completion of this development is a change in direct and indirect costs which will affect the cost of this Kraton Market Revitalization. The total cost of this Kraton Market Revitalization plan is Rp. 4,050,750,000.00 with details of direct costs of Rp. 3,790,134,382.00 and indirect costs of Rp. 260.615618.00. This study uses 2 alternative accelerations, namely the addition of 3 hours of overtime per day and the addition of workers, with a target time of project completion on December 28, 2019, initial plan. Then the researcher will compare the costs that must be incurred by the contractor either by using additional working hours or additional labor against if the project is not controlled and has the potential to be late. In this study, researchers used the Microsoft Project 2019 tool to create a network and to search for critical activities in this Kraton Market Revitalization project. The conclusions obtained from the research are: (1) If the project implementation is not controlled, it will be 10 days late from the plan and potentially result in the total cost being Rp. 4.111.001.107.42. (2) With the alternative of additional working hours (overtime), the completion on time according to the plan with a total cost of Rp. 4,095,530,798.10. (2) With the alternative of additional manpower, the timely completion according to the plan with a total cost of Rp. 4,051,228,691.86. according to the